2016
DOI: 10.1556/084.2016.17.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Eating and drinking seen through translation: A study of food-related translation difficulties and techniques in a parallel corpus of literary texts

Abstract: This paper presents an exploratory study on translators' decisions when encountering foodrelated translation difficulties in a parallel corpus of German original narrative texts and their translations into Spanish and Catalan. For this purpose, all food and drink related lexemes in the German original texts were extracted and classified in semantic groups. As a second step, the source and target text fragments of lexemes related to food-related cultural referents, metaphorical expressions or ways of eating and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 20 publications
1
9
0
1
Order By: Relevance
“…(g) Omission : this involves eliminating ST CSI from the target text or removing items that are considered unimportant and redundant from the translation (Marco, 2019; Oster & Molés-Cases, 2016, p. 60). While omission is very often linked to the admission of defeat by the translator in rendering a word that may be untranslatable, Baker (1992) correctly asserts that in some cases, omission can be a viable translation decision when “the meaning conveyed by a particular item or expression is not vital enough to the development of the text to justify distracting the reader with lengthy explanations” (p. 40).…”
Section: Translation Of Culture-specific Itemsmentioning
confidence: 99%
“…(g) Omission : this involves eliminating ST CSI from the target text or removing items that are considered unimportant and redundant from the translation (Marco, 2019; Oster & Molés-Cases, 2016, p. 60). While omission is very often linked to the admission of defeat by the translator in rendering a word that may be untranslatable, Baker (1992) correctly asserts that in some cases, omission can be a viable translation decision when “the meaning conveyed by a particular item or expression is not vital enough to the development of the text to justify distracting the reader with lengthy explanations” (p. 40).…”
Section: Translation Of Culture-specific Itemsmentioning
confidence: 99%
“…Li (2019) found that translating Chinese food names into English could use intralingual translation, interlingual translation and intersemiotic translation, but the research was from a macro perspective and did not show the specific techniques for food translation. Oster and Molés-Cases (2016) applied intracultural and intercultural adaptation, neutralization, omission, re-creation and literal translation to translate food-related culturemes, but the focus was on parallel corpus from literary texts. A discussion was made on the translation techniques of food-related culturespecific items (Marco, 2019), which shed light on this current study by the application of borrowing, literal translation, neutralization, amplification, omission, intracultural adaptation and intercultural adaptation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Marco's (2019) borrowing technique contained Reynolds's (2016) transliteration, as Dong (2021) stated that borrowing technique included natural borrowing (also called transliteration) and direct borrowing. Secondly, some scholars adopted Marco's (2004) taxonomy on food-related translation, such as Oster and Molés-Cases (2016). Through the time of 2004 and 2019 is different, the techniques used in Oster and Molés-Cases's (2016) study are similar with the version of Marco (2019).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Delia Chiaro ve Linda Rossato, 2015 yılında The Translator dergisi için hazırladıkları "Yemek ve Çeviri" başlıklı özel sayı için yazdıkları sunuş makalesinde, yemek metinlerinin çevirisiyle ilgili pazarın hızla büyümesine rağmen çeviribilim alanında bu konuda yapılan araştırmaların oldukça az olduğunu vurgular (Chiaro & Rossato, 2015: 237). Ancak son yıllarda çeviribilim alanında da bu konuda yapılan çalışmaların hızla arttığı söylenebilir (örneğin Chiaro 2008;Chiaro & Rossato 2015;Cronin 2015Cronin , 2017De Marco 2015;González-Vera 2015;Rossato 2015;Oster & Molés-Cases 2016;Stano 2016;Vidal Claramonte & Faber 2017;Beyaz 2017;Ciribuco 2019).…”
Section: Adressunclassified